Páginas iniciais - sumário bilíngue, Ficha catalográfica e (Redes, 2014)
REDES, Santa Cruz do Sul, v. 19, nº 1, p. 1 - 296 , jan/abril 2014. ISSN: 1982-6745 Editores Virginia Elisabeta Etges Marco André Cadoná